A compact implantable RFID tag antenna dedicated to wireless health care. Issue 5 (6th February 2017) - Aslam, Bilal; Khan, Umar Hasan; Azam, Muhammad Awais; Amin, Yasar; Loo, Jonathan; Tenhunen, Hannu
Abstract: Implantable tag antennas are an integral component of contemporary pervasive patient monitoring setups envisioned to reduce the medical errors and improve the quality of health care facilities. These tags, embedded into the human body, transmit critical patient information to the external equipment via a wireless communication link. This research article presents an implantable compact folded dipole antenna of size 10 mm × 15 mm × 2 mm, designed to operate in the industrial‐scientific‐medical band (2.4‐2.48GHz). A three‐layered phantom representing the human arm is used to evaluate the subcutaneous antenna performance. The tag antenna embedded in the middle of the fat layer offers a maximum gain of −16.3 dBi. The tag antenna performance as a function of implant position and phantom dimensions is analyzed. Link budget calculations show that with the achieved antenna gain the link power exceeds the required power by 38.37 dBm, and hence wireless communication is viable.